2017
DOI: 10.21746/ijcls.2017.6.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Study of chloride concentration of Nira River, Pune, Maharashtra, India.

Abstract: The present work deals with the study of Chloride concentration of Nira River in the year 2016. Fresh water is essential to existence of life. Acceptable quality water is essential not only for drinking and domestic purposes but also for agriculture, industrial and commercial uses. Chloride occurs naturally in all types of water. In natural fresh water, the concentration is quite low. The important source of chloride in the water is the discharge of domestic sewage. Chlorides are highly soluble in water so the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Chlorides are present in all natural waters. Fresh water sources contain chlorides ranging from 100 to 200 mg/L [24,26]. Here, observed values are in the range of 29 to 279mg/L.…”
Section: Resultsmentioning
confidence: 74%
“…Chlorides are present in all natural waters. Fresh water sources contain chlorides ranging from 100 to 200 mg/L [24,26]. Here, observed values are in the range of 29 to 279mg/L.…”
Section: Resultsmentioning
confidence: 74%
“…It has been reported that the discharge of industrial wastes and domestic sewage could increase the concentration of sulphates in water [1]. Sulphate may have a laxative effect that can lead to dehydration and is of particular concern for infants [46].…”
Section: Resultsmentioning
confidence: 99%
“…The numbers of landfills, oil fields, military installations, private properties, manufacturing and industrial contaminated sites are staggering, globally. Traces of pesticides, oil and greases, heavy metals and other toxic chemicals together with high chloride concentrations and low dissolved oxygen levels (0.75 mg/L) in water aquifers were recently reported by Jadhav et al (2013). Leachate produced by a municipal solid waste landfill sites had reported to have had a profound impact on surrounding shallow basaltic aquifers where physio-chemical parameters for groundwater reported high concentrations of heavy metals including Al, Cd, Cr, Fe, Zn, Ni and Pb in water (Kale et al, 2010).…”
Section: Nanoparticles and Environmental Remediationmentioning
confidence: 95%